Synthesis and characterization of metal complexes derived from Codeine - Zebiri, Yacine; Saïdat, Boubakeur (Laghouat : Université Amar Telidji - Département des sciences de la matière, 2025)
Codeine has many medical uses, such as pain relief and cough medicine. This study focused on the synthesis of complexes between codeine and metals. The published structure of the codeine-Fe(III) complex by (Ghamami et al). was used as the starting point for this study. First, the compound itself was modeled using DFT and NEB methods to evaluate its stability and energy interaction properties. Then, the Fe(III)-codeine compound was synthesized Practical, and different organic solvents were tested in the complex formation to evaluate the effect of the medium on the result. The resulting precipitates were then analyzed using UV-visible and FTIR spectroscopy. An attempt was made to synthesize complexes between pure codeine and codeine phosphate with different metal ions such as Fe²⁺, Cu²⁺.Two methods were used to synthesize the complexes: the first in an organic medium (method 1) and the second in an aqueous medium with heating (method 2). The resulting precipitates were evaluated in terms of color and yield. The products were analyzed using FTIR and showed signs of possible codeine-metal coordination in several cases, although the nature of the resulting precipitates remained inconclusive in some cases. Overall, this study demonstrates the possibility of forming codeine-metal complexes, and may serve as a starting point for pharmacological research based on the synthesis of new stable complexes.